2015
DOI: 10.2217/imt.14.123
|View full text |Cite
|
Sign up to set email alerts
|

CAR T-cell Therapy: Toxicity and The Relevance of Preclinical Models

Abstract: Chimeric antigen receptor (CAR) T cells form part of a broad wave of immunotherapies that are showing promise in early phase cancer clinical trials. This clinical delivery has been based upon preclinical efficacy testing that confirmed the proof of principle of the therapy. However, CAR T-cell therapy does not exist alone as T cells are generally given in combination with patient preconditioning, most commonly in the form of chemotherapy, and may also include systemic cytokine support, both of which are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 61 publications
0
51
0
2
Order By: Relevance
“…4,5,7-11,13-16, [35][36][37][38][39][40] Neurologic toxicities due to CAR T-cell therapy may occur concurrently with CRS or occur in the absence of CRS. 4,5,15 Hypothetically, the gene-therapy vector could be capable of autonomous viral replication or cause a secondary malignancy through insertional mutagenesis.…”
Section: -30mentioning
confidence: 99%
“…4,5,7-11,13-16, [35][36][37][38][39][40] Neurologic toxicities due to CAR T-cell therapy may occur concurrently with CRS or occur in the absence of CRS. 4,5,15 Hypothetically, the gene-therapy vector could be capable of autonomous viral replication or cause a secondary malignancy through insertional mutagenesis.…”
Section: -30mentioning
confidence: 99%
“…Adverse events such as severe CRS have been associated with the administration of CAR-T cells to patients with high tumor burden, which likely triggers massive antigen-specific CAR-T-cell expansion and activation (4,41). Therefore, we next asked whether the switch could be dose-titrated to achieve a gradual tumor clearance to avoid the acute toxicity.…”
Section: Effect Of Fitc Conjugation Site and Valency On Anti-fitc Carmentioning
confidence: 99%
“…Collectively, our results demonstrate that the activity of sCAR-T cells can be controlled by switch dosage to minimize treatment-related toxicities while retaining potent antitumor activity. This ability to control the temporal activation of the CAR-T-cell response may be helpful clinically to ameliorate adverse events associated with the administration of CAR-T cells to patients with high tumor burden, such as severe CRS (4,41).…”
Section: Effect Of Fitc Conjugation Site and Valency On Anti-fitc Carmentioning
confidence: 99%
“…Moreover, a preclinical study showed that 3rd-G CAR-T cells combining CD28 and 4-1BB co-receptors had superior in vitro activation and proliferation capacity compared with 2nd-G CAR-T cells carrying CD28 signal domains, and both kinds of cells displayed in vivo comparable efficacy in eliminating CD19+ B cells 35. Another preclinical study demonstrated that in vivo persistence of 3rd-G CAR-T cells was inferior to that of 2nd-G ones 41. But there is a lack of clinical data of 3rd-G CAR-T cells in patients.…”
Section: Discussionmentioning
confidence: 99%
“…For one, engrafted human CAR-T cells may be challenged by residual elements of the immune system from immunocompromised mice. For another, it is difficult to assess CAR-T toxicity because human CD19 expression profile may not be equivalent to that of mouse 41. Therefore, the ability to predict and manage severe CRS in clinical trials is vital to protect patients' interests because early interventions could limit the efficacy of CAR-T immunotherapy while the late ones could increase morbidity and mortality of treated patients.…”
Section: Discussionmentioning
confidence: 99%